THE EFFORT OF THE EDUCATORS ON BUILDING POSITIVE CHARACTER ON EARLY CHILDHOOD STUDENT THROUGH ISLAM EDUCATION AT RAUDATUL ATHFAL IDAMAN - Dwi Hayantini Sunarti (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
Childrens is a mandate from Allah SWT that entrusted to all parents which will eventually be asked for responsibility. Every childrens born pure and clean,  both parents is making them into Jewish, Christian, Magi (HR Bukhari Muslim). So that childrens is a very weak person that will always rely to every human being around them. Physically one children is a base that can be build into so many shapes. Therefore all the childrens need a serious attentions, since every childs will absorbed everythings they see or hear because they have no power to refuse it. So it has become the responsibility of the parents or the people around them to give the attention about religious issues include, faith, worship, and morals. Because religion is a guideline to every humans life whether in this world and hereafter, so that its very affect every aspect in humans life whether its body or its soul. Every childrens that has potention from the day they born is possible to grow and can be fostered with religious values from an early age. If not properly fostered the period of physical and psychological development will be missed. This will be very harmful to every childrens, because if the development of their religious souls is good, they will keep it in their heart and will got an amazing values in their future. Al Qur’an saids that educations is one of the effort that will lead every human being to the way of Allah SWT with a thoughtfull ways, good advice will come with a good point of view too. Educations is a thing to one effort or process which held with consiousness, planned well and responsible, so that this required an educations method that fit perfectly to the target or an educations purpose that want to be achieve. The essence of religious educations is the foundations of religious morality to the childrens, while teaching is to give a knowledge to the protégé. Religious educations basically is to train (continue) rligious purity that every childs have since their birth, so that wont fade into atheism or even turn Into other religion except Islam. So that need to be our concern to habituate every child to do their responsibility to implement religious law and to stay away from its prohibition.